Peer Feedback on Collaborative Learning Activities in Veterinary Education - Laura M. Dooley; Nicholas J. Bamford (Veterinary Sciences, 2018)
Collaborative learning activities are an increasingly prominent feature of veterinary curricula that have been redesigned to achieve competency-based graduate learning outcomes. This evolution challenges the traditional individualistic approach to veterinary education and necessitates revisions to assessment and feedback practices to ensure constructive alignment. Peer feedback has been widely reported in the medical education literature as a teaching intervention in collaborative learning settings, with learning gains reported for students who receive and provide peer feedback. In this setting, peer feedback has been demonstrated to provide valuable formative feedback on professional behaviors and skills. However, there are very few such reports in the veterinary education literature to date. Barriers to the introduction of this approach can include teacher and student perceptions, and concerns around validity and reliability. This review aimed to provide an overview of current evidence regarding peer feedback on collaborative learning activities in higher education, and to explore opportunities and challenges for the introduction of peer feedback in the context of veterinary education. We contend that early and repeated provision of formative peer feedback can provide an opportunity to scaffold the development of crucial core competencies within veterinary education, including the self-regulated learning skills required to work in collaborative teams, and interpret and act on feedback.